The relationship between standing broad jump and 30-meter sprint in 826 youth soccer players: a cross-sectional study - Škorik, M.; Švantner, R.; Brunn, D.; Karabin, L. (The Journal of Strength and Conditioning Research, 2026)
Speed and acceleration are essential for offensive and defensive actions in soccer. Given the high cost of advanced sprint measurement systems, alternative field tests such as the standing broad jump (SBJ) may serve as cost-effective tools for assessing horizontal force production. However, the relationship between SBJ and sprint performance across different acceleration phases in youth players remains unclear. This cross-sectional study investigated the relationship between a no-countermovement SBJ and sprint parameters in 826 elite male youth soccer players (U14-U19). Sprint performance was assessed using the 1080 Motion Sprint system, capturing maximum velocity (Vmax), theoretical maximum velocity (V0), maximum horizontal force (F0), maximum power, and maximum ratio of force (RFmax). Average speed (AS) and average force (AF) were analyzed across 3-meter segments for a 30-meter sprint. Pearson's correlation and linear regression were used, with significance set at p <= 0.05. Standing broad jump showed strong correlations with sprint parameters, particularly Vmax, V0, and RFmax (r = 0.68, 0.63, and 0.58; all p < 0.001). The strongest associations between SBJ and AS or AF occurred in the late acceleration phase (9-12 m) across all age groups (AS: r = 0.75; AF: r = 0.66), with the highest correlations in U14 and U15. Regression models revealed that SBJ explained 39.1% of Vmax variance in U14, but only 9.8% in U19. These findings suggest SBJ is a practical and valid tool for evaluating sprint performance in younger players, although its predictive value declines with age because of greater influence of technical and biomechanical sprint factors.